2009
DOI: 10.1371/journal.ppat.1000492
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Latency in B Cells Leads to Epigenetic Repression and CpG Methylation of the Tumour Suppressor Gene Bim

Abstract: In human B cells infected with Epstein-Barr virus (EBV), latency-associated virus gene products inhibit expression of the pro-apoptotic Bcl-2-family member Bim and enhance cell survival. This involves the activities of the EBV nuclear proteins EBNA3A and EBNA3C and appears to be predominantly directed at regulating Bim mRNA synthesis, although post-transcriptional regulation of Bim has been reported. Here we show that protein and RNA stability make little or no contribution to the EBV-associated repression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 54 publications
7
163
0
1
Order By: Relevance
“…H These 2 insertions (changing 7 consecutive T residues to 8) are the same, but are included as potential mutations as they occurred in 2 clearly distinct genetic backgrounds (Supplemental Figure 5C). I Described in detail previously (53).…”
Section: Ebna3bko-transformed B Cells Have a Growth Advantage In Vitrmentioning
confidence: 99%
“…H These 2 insertions (changing 7 consecutive T residues to 8) are the same, but are included as potential mutations as they occurred in 2 clearly distinct genetic backgrounds (Supplemental Figure 5C). I Described in detail previously (53).…”
Section: Ebna3bko-transformed B Cells Have a Growth Advantage In Vitrmentioning
confidence: 99%
“…EBNA3C or EBNA3A have many specific and potentially significant interactions with other transcription factors or modifiers, including PU.1, Spi-B, HDAC1, DP103, prothymosin-α, p300, Nm23-H1, SUMO1, and SUMO3, cyclin A, SCF SKP2 ubiquitin ligase, pRb, Chk2, Mdm2, and MRS18-2, and these interactions could be relevant to CDKN2A p16 INK4A or p14 ARF regulation and LCL growth (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Furthermore, EBNA3C upregulates TCL1A and ITGA4, down-regulates JAG1 and NCALD RNAs, and cooperates with EBNA3A in repressing Bim, a proapoptotic Bcl-2 family protein (24,(39)(40)(41). Indeed, EBNA3C and EBNA3A may cooperatively repress the p16 INK4A and p14 ARF tumor suppressors to allow cell cycle progression, as is required for MYC conversion of tissue cells to stem cells, for HPV16-and HPV18-induced cervical cancer, and for other enforced cell proliferations (42)(43)(44).…”
mentioning
confidence: 99%
“…Most reports show that BIM is a key regulator of life and death decisions (Anderton et al, 2008;Paschos et al, 2009). Thus, it is not surprising that EBV BHRF1 binds to the BH3-only peptide BIM and interacts strongly with its protein (Flanagan and Letai, 2008).…”
Section: Bhrf1 Binds To Bimmentioning
confidence: 99%
“…What is more, EBNA3C is directly targeted to the BIM promoter (Paschos et al, 2012). Previous research has shown that in the 5′ regulator region of BIM, heritable epigenetic modifications initiated by EBNA3A and EBNA3C play a major role in determining the level of post-transcriptional BIM production expressed in EBV-infected B cells (Paschos et al, 2009). …”
Section: 2mentioning
confidence: 99%